2019
DOI: 10.1186/s12960-019-0436-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternity waiting homes on the health workforce and maternal health service delivery in rural Zambia: a qualitative analysis

Abstract: BackgroundMaternity waiting homes (MWHs) are a potential strategy to address low facility delivery rates resulting from access-associated barriers in resource-limited settings. Within a cluster-randomized controlled trial testing a community-generated MWH model in rural Zambia, we qualitatively assessed how MWHs affect the health workforce and maternal health service delivery at their associated rural health centers.MethodsFour rounds of in-depth interviews with district health staff (n = 21) and health center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…While midwives were briefed on use of MWH registers and their continued role in referring women to MWHs, they were not provided additional training as part of the intervention. While it is unlikely that upgraded MWHs increased delivery workloads substantially as reported in other settings [ 52 ], more engagement with midwives may have improved levels of MWH user monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…While midwives were briefed on use of MWH registers and their continued role in referring women to MWHs, they were not provided additional training as part of the intervention. While it is unlikely that upgraded MWHs increased delivery workloads substantially as reported in other settings [ 52 ], more engagement with midwives may have improved levels of MWH user monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In previous findings, health system stakeholders had similarly described the importance of the GCMU because its presence allows health system staff to attend to their clinical duties. 32 Although the community representatives on the GCMU are the instrumental link to the community, the health facility staff is the instrumental link to the district and government-level actors. This governing body where community representatives and health facility staff formally collaborate to ensure the smooth operations of the MWH serves as a key opportunity to connect the community with the formal health system.…”
Section: Discussionmentioning
confidence: 99%
“…34 It is also worth noting that even though respondents were blind to the official outcomes, such as district-wide skilled birth attendance rates, many respondents perceived the intervention to have had positive outcomes on maternal mortality and have been beneficial to the community. 32 We hypothesize that the sense of ownership may be stronger if the intervention is perceived to have a positive impact on maternal child health outcomes because community members would want to sustain these effects and the MWH model. We had posited that the intervention would continue after the end of the external support period, in part due to the project's goal of fostering community ownership.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by various studies, women reported MWHs as very important institutions to creating opportunities for and facilitating communication platforms between providers and mothers to elevate trust, build mothers' con dence, and promote bonding (23) (24) (25). Additionally, they help health workers to adjust their schedule and ensure the availability of the required supplies and drugs (26).…”
Section: Discussionmentioning
confidence: 99%